Intake and feed utilization in two breeds of pregnant beef cows fed forages with high-fiber concentrations() - Jardstedt, Mikaela (J Anim Sci, 2018)
Hereford and Charolais beef cows (n = 24 per breed) were used to study the effect of breed and to evaluate late-cut reed canarygrass (RC) and whole-crop oats plus urea (WCO) compared with late-cut timothy (TG) with respect to feed intake and digestibility, rumination time, fecal particle size (PS) distribution, N excretion, and ruminal microbial CP production (MCP). The TG and RC were cut at flowering and WCO at hard dough stage of maturity. Cows were group-housed, 6 groups per breed, and fed 3 diets ad libitum in 3 periods. The study was designed as two 3 × 3 Latin squares amalgamated to form a 3 × 6 rectangle for each breed. All data were statistically analyzed on group level. Indigestible NDF (iNDF) and urinary creatinine excretion were used as markers to estimate apparent diet digestibility and daily urine volume, respectively. Fecal PS distribution was determined by dry sieving, and ruminal MCP synthesis was estimated based on urinary output of purine derivatives. The TG diet had a higher apparent digestibility of OM and NDF (P < 0.001) than RC and WCO, which did not differ. The TG diet resulted in the greatest daily DMI, followed by WCO and RC (P < 0.001). Intake of NDF (NDFI, kg/d and % of BW) was greatest for TG, followed by RC and WCO (P < 0.001). Rumination time per kg DMI was longest for RC (P < 0.001), and RC and WCO resulted in longest rumination time per kg NDFI (P < 0.001). The WCO diet resulted in the largest geometric mean fecal PS and proportion of large particles and in the smallest proportion of small particles, whereas the opposite was found for RC, with TG being intermediate (P < 0.001). Intakes in kg per day were higher for Charolais than for Hereford (P = 0.002), but no breed effect was detected when intake was expressed in relation to BW. Charolais ruminated longer per kg NDFI corrected for BW (P = 0.02) and had smaller mean fecal PS (P = 0.049) than Hereford. Total N excretion was highest for RC and lowest for WCO (P < 0.001). The TG diet stimulated MCP production to a greater extent than RC and WCO (P < 0.001). The results indicate that late-cut RC and WCO could be suitable alternatives to late-cut TG for ad libitum feeding of early pregnant beef cows, and that intake was associated with cow BW, but not with breed. The variations in NDF and iNDF concentrations between forage diets were reflected in their effects on intake, rumination, apparent digestibility, and fecal PS.